TANTANGAN IBU SINGLE PARENT DALAM MEMENUHI HAK ANAK PERSPEKTIF PERLINDUNGAN ANAK DAN KESEJAHTERAAN IBU - Ainun qholby; Khoriyah Harun (Jurnal Risalah Addariyah: Studi Ilmu-Ilmu Keislaman, Pendidikan dan Sosial Kemasyarakatan, 2024)
The purpose of this study is to identify the main challenges faced by single-parent mothers, analyze the impact of these challenges on children's welfare, evaluate the effectiveness of existing policies in protecting and supporting single-parent mothers, and develop recommendations that can be implemented by policymakers, government, and social organizations to improve support for single parent mothers. The research method used in this study is qualitative with a case study approach. This method allows researchers to gain an in-depth understanding of the experiences and challenges faced by single-parent mothers. Data were collected through in-depth interviews with single-parent mothers as well as through a review of relevant literature. This study revealed several relevant results. First, the main challenges faced by single-parent mothers include financial problems, difficulties in managing time, physical and mental exhaustion, and lack of social support. Secondly, this study shows that existing policies to protect and support single-parent mothers have not been fully effective. Therefore, a more in-depth policy evaluation is needed to improve its effectiveness. Based on the results of this study, the researcher also developed recommendations that can be implemented by policymakers, the government, and social organizations. These recommendations aim to improve support for single-parent mothers and ensure that children's rights are fulfilled by Indonesia's Child Protection Law.